Determinación de la estabilidad del virus Chikungunya en hemocomponentes almacenados en condiciones estándar de banco de sangre (2023)
The Chikungunya virus circulates in tropical and subtropical regions of the planet, in recent decades has increased its incidence where its adaptation to urban environments is highlighted generating a greater spread, which becomes a focus of attention for public health, leading to establish strategies to contain the expansion. In addition to this concern, studies have been carried out in different parts of the world to determine whether arboviruses can be transmitted through blood transfusions, indicating that there is a considerable risk of transmission by this route. It is known that Colombia is an endemic country and does not have information or reports that determine the great risk to which the population receiving hemocomponents is exposed, the concern is focused on those patients who become asymptomatic or have mild symptoms, could donate blood with a significant viral load to infect a patient. According to the aforementioned, we evaluated the possible variations of the viral load of Chikungunya virus in hemocomponents stored under standard blood bank conditions, to fulfill our objective, we used units of red blood cells and platelets supplied by the blood bank, which were infected with 2.5x103 PFU/mL of Chikungunya virus to subsequently measure the viral load at different times by means of the RT-qPCR technique. The results obtained allowed determining that on most days the Chikungunya viral load had a tendency to decrease, accentuated on days 4 and 5 in platelets, the statistical analysis indicated significant differences except on day 6. In red blood cells, the trend had a behavior with slight variations compared to platelets, where there was a significant increase in the viral genome between days 14 and 21.